PENGEMBANGAN LEMBAR KERJA MATERI MENULIS TEGAK BERSAMBUNG PADA PESERTA DIDIK KELAS II SDN 3 BULANGO UTARA - Nadia Alzahra Dondo; Rusmin Husain; Fidyawati Monoarfa; Wiwy T. Pulukadang; Rustam I. Husain (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop Student Worksheets (Lembar Kerja Peserta Didik) for the topic of cursive handwriting (connected upright letters) for second-grade students at SDN 3 Bulango Utara. The background of this research is based on the low level of students' cursive writing skills, which is attributed to the limited availability of instructional materials, particularly the absence of specifically designed and systematic worksheets. Additionally, the learning process still heavily relies on standard student textbooks, leading to boredom and decreased learning motivation among students. This study employs a Research and Development (R&D) method using the ADDIE development model, which consists of the stages of Analyze, Design, Development, Implementation, and Evaluation. The subjects of this research are second-grade students at SDN 3 Bulango Utara. Data collection techniques include observation, questionnaires, and documentation, while data analysis is conducted to determine the feasibility, practicality, and effectiveness of the developed worksheets. The results indicate that the developed student worksheets for cursive handwriting are feasible to be used as learning media, practical in their implementation, and effective in improving students’ cursive writing skills. Therefore, the developed worksheets can serve as an alternative instructional material to support Indonesian language learning in elementary schools, particularly in enhancing students’ early writing skills.